2014
DOI: 10.1109/tps.2014.2334601
|View full text |Cite
|
Sign up to set email alerts
|

Drifting Ionization Zone in DC Magnetron Sputtering Discharges at Very Low Currents

Abstract: Fig. 1. False-color fast camera images of aluminum sputtered in 0.5 Pa of argon. The top 8 images show the blurring of a drifting ionization zone when the image exposure time exceeds 5 μs (the discharge current was 30 mA). The center 4 side-view images were taken with an exposure time of 500 ns for different discharge currents; z is the distance from the target surface. The lower 4 images, also taken with 500 ns exposure time, illustrate the existence of one zone at different currents. Note that the camera was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…6,7 In both regimes, ionization zones are observed for a wide range of discharge conditions. Ionization zones are stochastic, evolving patterns which occasionally become periodic, indicating selforganization of magnetron plasma.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 In both regimes, ionization zones are observed for a wide range of discharge conditions. Ionization zones are stochastic, evolving patterns which occasionally become periodic, indicating selforganization of magnetron plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Spokes can be found in high power impulse magnetron sputtering (HiPIMS), 1,2 as well as in the more traditional direct current magnetron sputtering (dcMS). 5 In HiPIMS, spokes drift in the E× B direction, i.e. the direction of the electron drift.…”
mentioning
confidence: 99%
“…As we know from probe measurements and fast frame camera imaging, 5,8,12 certain power and pressure conditions lead to one, two, or more spokes that are relatively stable as they move along the racetrack, while other parameter combinations exhibit less stability. Fig.…”
mentioning
confidence: 99%
“…spokes 11,16,17 ), and associated potential humps. 18 Fast imaging of HiPIMS [2][3][4]11,19 and direct current magnetron sputtering 20 (dcMS) plasmas indicated that ionization rate and emission of light and particles are usually not uniformly distributed but concentrated in bright zones that move along the racetrack. Additionally, measurements of charged particle fluxes have revealed important features: (a) ion and electron fluxes appear in short pulses (jets), 21 (b) doubly charged ions have approximately twice the energy of singly charged ions, 18,21 and (c) ions emitted in the E× B direction have several 10 eV higher energy than ions going in the opposite direction, i.e., leaving the magnetron in the −E× B direction.…”
mentioning
confidence: 99%